Validation‐Based Insertional Mutagenesis (VBIM), A Powerful Forward Genetic Screening Strategy. Issue 3 (22nd March 2022) - De, Sarmishtha; Tamagno, Ilaria; Stark, George R.; Jackson, Mark W.
Abstract: Forward genetics begins with a biological phenotype and attempts to identify genetic changes that influence that phenotype. These changes can be induced in a selected group of genes, for instance, by using libraries of cDNAs, shRNAs, CRISPR guide RNAs, or genetic suppressor elements (GSEs), or randomly throughout the genome using chemical or insertional mutagens, with each approach creating distinct genetic changes. The Validation‐Based Insertional Mutagenesis (VBIM) strategy utilizes modified lentiviruses as insertional mutagens, placing strong promoters throughout the genome. Generating libraries with millions of cells carrying one or a few VBIM promoter insertions is straightforward, allowing selection of cells in which overexpression of VBIM‐driven RNAs or proteins promote the phenotype of interest. VBIM‐driven RNAs may encode full‐length proteins, truncated proteins (which may have wild‐type, constitutive, or dominant‐negative activity), or antisense RNAs that can disrupt gene expression. The diversity in VBIM‐driven changes allows for the identification of both gain‐of‐function and loss‐of‐function mutations in a single screen. Additionally, VBIM can target any genomic locus, regardless of whether it is expressed in the cells under study or known to have a biological function, allowing for true whole‐genome screens without the complication and cost of constructing, maintaining, and delivering a comprehensive library. Here, we review the VBIM strategy and discuss examples in which VBIM has been successfully used in diverse screens to identify novel genes or novel functions for known genes. In addition, we discuss considerations for transitioning the VBIM strategy to in vivo screens. We hope that other laboratories will be encouraged to use the VBIM strategy to identify genes that influence their phenotypes of interest. © 2022 Wiley Periodicals LLC.